A garota-propaganda Lu: A apropriação de imaginários no avatar do Magalu como estratégia narrativa no pós-digital - Martins , Israel Conde Aleixo (2024)
A narrative advertising has shown itself, over the decades, capable of developing dialogues beyond the sole purpose for which it was created. Evolving its techniques to keep pace with each new media landscape, today we are faced with a communication overflowing in engaging with social imaginaries. Appropriating them, fostering them, and participating in the everyday scene in a way that is no longer exclusively commercial. One of the phenomena we have witnessed is the communication carried out by avatars that simulate humans. A practice that prompts us to reflect on how a brand can shape its positioning through a virtual figure, to the extent that its creation can reach a scale akin to a physical and real personality. This study articulates theories that allow us to better understand the performance of the Lu avatar, created by Magazine Luiza, representing the brand's values organically within a complex discursive structure. The aim is to provide a procedural overview of the maturation of advertising text, in line with Rocha (2010) and Carrascoza (2006). Subsequently, it reflects on how a "wearing out" of digital consumption logics has given rise to the concept of post-digital, according to Cramer (2017). Following this, a semiotic analysis is conducted that examines the narrative progression through its various stages in light of structuralist theory, following an adapted analysis protocol from Greimas' generative trajectory of meaning (1983). Lastly, it delves into the performance of Lu from Magalu as a rhetorical concept in Aristotle and its externalization from the perspective of Maingueneau (2008). This advertising enunciation case demonstrates discursive competence for understanding, above all, the communicational and social relationships of our time.